N-acetyl cysteine in ovulation induction of PCOS women underwent intrauterine insemination: An RCT - Tahereh Behrouzi Lak; Masoomeh Hajshafiha; Fariba Nanbakhsh; Sima Oshnouei (Shahid Sadoughi University of Medical Sciences, 2017)
Background: N-acetyl cysteine (NAC) was proposed as an adjuvant to clomiphene citratefor ovulation induction in patients with polycystic ovary syndrome (PCOS) without clomiphene citrate resistance. Objective: To evaluate the effect of NAC on pregnancy rate in PCOS patients who were candidates for intrauterine insemination. Materials and Methods: In this randomized clinical trial 97 PCOS women aged 18-38 years were enrolled in two groups, randomly. For the case group (n=49), NAC (1.2 gr)+ clomiphene citrate (100 mg) + letrozole (5mg) were prescribed Daily from the third day of menstruation cycle for five days. The control group (n=48) had the same drug regimen without NAC. In order to follicular development, GONALF was injected on days of 7-11 menstrual cycles in all participants. When the follicle size was 18mm or more, HCG (10000 IU) was injected intramuscular and the intrauterine insemination was performed after 34-36 hr. Results: There were not significant differences between study groups regarding mean endometrial thickness (p=0.14), mean number of mature follicles (p=0.20) and the pregnancy rate (p=0.09). Conclusion: NAC is ineffective in inducing or augmenting ovulation in PCOS patients who were candidates for intrauterine insemination and cannot be recommended as an adjuvant to CC in such patients.